IDENTIFICATION OF SOCIAL SYMPTOMS USING THE DRONE EMPRIT ACADEMIC AS A SUPPORT FOR STATISTICAL LITERACY - Waluyo Satrio Adji; Abdul Bashith; Ali Nasith; Saiful Amin (Abjadia : International Journal of Education, 2019)
Social problems in Indonesia in particular are caused by social phenomena transmitted to users of social media, especially Twitter. Big data system provided by Drone Emprit Academic is able to find social phenomena. The ability of critical literacy to read and write supported by statistical data is very important in the 4.0 era. The aim of the research is to find out which Drone Emprit Academic works, analyzes, and displays data on social phenomena whose results can be used to support critical Literacy. This research uses a qualitative approach, literature study method. The analysis includes three stages, namely organize, synthesize, identify. The results of this study that Drone Emprit Academic is a big data system that carries out social network analysis of specific conversations on Twitter in semi-realtime and detail. The form displayed is in the form of a percentage of trends, retweet relationships, mentioning trend graphs, most retweet statuses, conversation trends. The data generated can help read information about social phenomena so that it can support critical literacy which has been partially published in online and offline media.